Poor sleep quality and associated factors among pregnant women in Ethiopia: A systematic review and meta-analysis - Agerie Mengistie Zeleke; Worku Chekol Tassew; Gashaw Melkie Bayeh; Yeshiwas Ayale Ferede (Elsevier, 2024)
Despite the associated health risks of poor sleep quality during pregnancy, recent evidence suggests that its impact persists in most countries. However, poor sleep quality during pregnancy in Ethiopia is poorly understood because of the lack of comprehensive reviews. Hence, we aimed to assess the pooled prevalence of poor sleep quality and associated factors among pregnant women in Ethiopia. Methods: A comprehensive search using electronic databases (PubMed, Cochrane Library, Google Scholar, and African Journal Online) was performed covering articles indexed before January 20, 2023. The quality of the included studies was evaluated using the Newcastle‒Ottawa Scale. Cochrane Q and I2 test statistics were used to examine the heterogeneity of the studies. A random-effects meta-analysis was performed with Stats Direct statistical software and Open Meta [Analyst] to estimate the prevalence of the outcome variable, and the results are reported in a forest plot. Simple charts and tables were used to summarize the evidence on poor sleep quality during pregnancy and its associated factors. Results: After 27,211 studies were reviewed, seven studies involving with 2689 study participants were included. The combined prevalence of poor sleep quality among pregnant women was 52.30 % (95 % CI: 42.39, 62.19). Depression (OR = 4.53; 95 % CI: 2.07, 9.89), perceived stress (OR = 3.42; 95 % CI: 2.46, 4.74), age greater than 35 years (OR = 3.47; 95 % CI: 1.01, 11.86), unplanned pregnancy (OR = 2.94; 95 % CI: 1.85, 4.68), anxiety (OR = 4.71; 95 % CI: 1.19, 18.65), and having poor sleep hygiene practices (OR = 4.32; 95 % CI: 1.48, 12.6) were significantly associated with poor sleep quality. Conclusions: More than half of the pregnant women did not have adequate sleep quality at night. Being depressed, stressed, anxious, having poor hygiene practices, and being older than 35 years were influential factors for poor sleep quality. Therefore, healthcare providers' regular early screening for poor sleep quality and its determinants is important for improving birth outcomes.